Influence of antidiabetic drugs on glucose metabolism and immune response in patients with metastatic pancreatic ductal adenocarcinoma receiving gemcitabine plus nab-paclitaxel as first-line treatment. Issue 5 (May 2023) - Pretta, Andrea; Ziranu, Pina; Giampieri, Riccardo; Donisi, Clelia; Cimbro, Erika; Spanu, Dario; Lai, Eleonora; Pecci, Federica; Balconi, Francesca; Lupi, Alessio; Pozzari, Marta; Persano, Mara; et al.
Abstract: Background: Association between pancreatic ductal adenocarcinoma (PDAC) and type 2 diabetes mellitus (DM2) has long been evaluated. Indeed, DM2 can be both an epiphenomenon of PDAC and a risk factor. The present study aimed to investigate the correlation between overall survival (OS) and antidiabetic drugs in patients with metastatic pancreatic ductal adenocarcinoma and DM2. Method: Data from 232 patients were collected retrospectively from 2014 to 2021. 174 from AOU Cagliari Medical Oncology and 58 from AOU Ancona Medical Oncology. All patients received gemcitabine plus nab-paclitaxel first-line chemotherapy. We aimed to evaluate the correlation between DM2, anti-diabetic medications and overall survival. Survival distribution was assessed by Kaplan-Meier curves. Results: Median age was 68±9, 127 (55%) were male. 138/232 (59%) patients were not affected by DM2, 94/232 (41%) were affected by DM2. 57 were insulin-treated and 37 were metformin-treated. DM2 treated patients showed an higher median overall survival (26 vs 12 months, p  =  0, 0002 ). Among DM2 patients insulin-treated and metformin-treated showed an mOS of 21 months and 33 months, respectively. Conclusions: Results showed a correlation between treated DM2 and higher mOS in patients with mPDAC. Limitations due to retrospective data collection must be considered. Further studies in this setting are needed.